SEROPREVALENCE AND RISK FACTORS ASSOCIATED WITH TOXOPLASMOSIS IN SHEEP IN MULTAN AND KHANEWAL DISTRICTS OF PUNJAB (PAKISTAN) - M. Hanif; Z. Tasawar (Journal of Animal and Plant Sciences, 2016)
During the present study 500 serum samples were examined to determine the seroprevalence of toxoplasmosis and risk factors in sheep by using latex agglutination test (LAT) and enzyme linked immunosorbent assay (ELISA) in Multan and Khanewal districts, Punjab (Pakistan).  The aim of the present study was to identify the potential risk factors associated with toxoplasmosis in sheep.  The overall seroprevalence was 33.6% by LAT and 27.4% by ELISA.  The area wise prevalence of toxoplasmosis was 34.02% and 33.01% by LAT and 28.12% and 26.41% by ELISA in Multan and Khanewal respectively.  Difference was statistically non-significant (P>0.05).  Out of 449 female sheep 60 were aborted. Relationship between toxoplasmosis and incidence of abortion indicated that seroprevalence was 51.66% and 41.66% in aborted sheep and 31.1% and 26.22% in non-aborted sheep by LAT and ELISA respectively.  Differences were statistically significant (P<0.05) by both techniques.  The results further revealed the non-significant differences between infection rates in males 31.37% and 19.6% and in females 33.85% and 28.28% via LAT and ELISA respectively.  The prevalence was higher in females than males and difference was statistically non-significant (P>0.05).  Relationship between age groups showed that toxoplasmosis prevalence was higher in age group 60-73 months (64.5% and 38.7% by LAT and ELISA respectively) and lowest in age group 4-17 months (26.4% and 22.4% by LAT and ELISA respectively) difference was statistically significant (P<0.05) by LAT and non-significant (P>0.05) by ELISA.  From the result of present study it is concluded that the large flock size, presence of cats, and the improper disposal of aborted fetuses openly left on ground were the main causes of higher rates of prevalence of toxoplasmosis in sheep which are potential threat of infection for human population of study area.
Keywords: Toxoplasma gondii; Sheep; sex; age; abortion; LAT; ELISA